The Impact of laparoscopic surgery of peritoneal endometriosis and endometrioma on the outcome of ICSI cycles. (3rd September 2017) - Guler, Ismail; Erdem, Ahmet; Oguz, Yuksel; Cevher, Funda; Mutlu, Mehmet Firat; Bozkurt, Nuray; Oktem, Mesut; Erdem, Mehmet
ABSTRACT: Our objective was to assess the role of laparoscopic removal of ovarian endometriomas and ablation of peritoneal endometriosis on the outcome of intracytoplasmic sperm injection (ICSI) - Embryo Transfer cycles by comparing with the results of patients with untreated endometriomas and tubal factor without underlying endometriosis confirmed by laparoscopy. For this purpose, between 2002 and 2015, outcomes of 257 ICSI cycles of 150 patients, including 91 cycles of 48 patients in minimal endometriosis, 57 cycles of 25 patients in endometrioma removal, 65 cycles of 53 patients in non-operated endometrioma, and 44 cycles of 24 patients in tubal factor groups were retrospectively analyzed. Basal ovarian reserve was significantly lower, mean starting and total gonadotropin consumption was significantly higher, and mean serum E2 on the day of hCG injection, number of dominant follicles, number of retrieved total, and MII oocytes were all significantly lower in the endometrioma cystectomy group. Fertilization and embryo cleavage rates were also significantly the lowest in the endometrioma cystectomy group, whereas clinical pregnancy and live birth rates were comparable among all groups. The number of transferred embryos and duration of infertility were the most significant predictors of clinical pregnancy and live birth. Basal antral follicle count was also significant in predicting live birth.